Manufacturing method for aluminum material
The electrolytic polishing method with controlled sodium chloride concentration and parameters in propylene glycol effectively addresses environmental and safety issues, producing a highly reflective aluminum surface.
Patent Information
- Application Number
- JP2023117061
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-30
AI Technical Summary
Existing electrolytic polishing solutions for aluminum materials pose environmental contamination risks due to phosphoric acid discharge and safety concerns with ethylene glycol, while achieving a mirror surface is challenging with propylene glycol under standard conditions.
An electrolytic polishing method using a propylene glycol solution with a specific concentration of sodium chloride (0.1 to 0.4 mol/l) and controlled parameters (temperature, voltage, and time) to form a mirror surface, defined by the equation E = (T × V × 1.23 × t) / (100000 × m), where E is between 6.5 and 100, ensuring low environmental impact and safety.
This method reduces environmental impact and improves safety by using propylene glycol, while achieving a highly reflective, mirror-like polishing surface on aluminum materials.
Smart Images

Figure 2025014478000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an aluminum material. [Background technology]
[0002] Conventionally, electrolytic polishing has been known as a method for manufacturing metal products such as aluminum materials having a polished surface. As electrolytic polishing liquids for aluminum materials, for example, electrolytic polishing liquids containing phosphoric acid and electrolytic polishing liquids containing perchloric acid are known. As such a technique, for example, the one described in Patent Document 1 is known.
[0003] However, when electrolytic polishing solutions contain phosphoric acid, if the phosphorus is discharged into the natural environment with wastewater, it may become a pollutant that leads to eutrophication of rivers and lakes. Also, electrolytic polishing solutions containing perchloric acid must be handled with care.
[0004] In response to these problems, Patent Document 2 describes an electropolishing solution containing ethylene glycol or propylene glycol as an electropolishing solution that has a lower environmental impact and is easy to handle. However, ethylene glycol is not preferred because it is less safe for the human body. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-006719 A [Patent Document 2] JP 2006-348336 A Summary of the Invention [Problem to be solved by the invention]
[0006] On the other hand, propylene glycol is safer than ethylene glycol. Therefore, it was expected that the use of an electrolytic polishing solution containing propylene glycol would reduce the environmental impact and improve safety. In this regard, Patent Document 2 describes the results of an experiment in which pure nickel was electrolytically polished using an electrolytic polishing solution containing propylene glycol.
[0007] However, even if the experimental conditions for pure nickel were simply applied to aluminum materials, the specularity was sometimes reduced, for example, white spots were generated on the surface of the aluminum material.
[0008] The present invention has been made in consideration of the above background, and aims to provide a method for manufacturing an aluminum material that reduces the environmental load, is easy to handle, has improved safety, and has improved specularity. [Means for solving the problem]
[0009] One aspect of the present invention is A method for producing an aluminum material having a polished surface formed by electrolytic polishing on a surface of a base material made of aluminum or an aluminum alloy, comprising: The base material is immersed in an electropolishing solution in which sodium chloride is dissolved in propylene glycol so that the concentration M of sodium chloride is 0.1 mol / L or more and less than 0.4 mol / L; The method for producing an aluminum material includes forming the polished surface on a surface of the base material by applying the electrolytic voltage to the base material as an anode and electrolytically polishing the base material under the condition that a parameter E represented by the following formula (1) is 6.5 or more and 100 or less, where T (unit: K) is the temperature of the electrolytic polishing solution, M (unit: mol / L) is the concentration of the sodium chloride, V (unit: V) is the electrolytic voltage, and t (unit: min) is the electrolytic time for electrolytically polishing the base material. E = (T × V 1.23 ×t) / (100000×M) ···(1) Effect of the Invention
[0010] According to one aspect of the present invention, by adopting conditions in which the concentration M of sodium chloride in the electropolishing solution and the value E in the formula (1) are within the specific range, electropolishing can be performed using propylene glycol, which has a low environmental impact, is easy to handle, and is highly safe. Furthermore, by performing electropolishing under the specific conditions, a polished surface with high specularity can be formed. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view of an aluminum material in the embodiment. [Diagram 2] FIG. 2 is an explanatory diagram of an electrolytic polishing apparatus in the embodiment. [Diagram 3] FIG. 3 is a SEM (scanning electron microscope) photograph showing white spots formed on the polished surface. [Figure 4] FIG. 4 is an enlarged SEM photograph of the white spots in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] (Aluminum material manufacturing method) In the method for producing an aluminum material, The base material is immersed in an electropolishing solution in which sodium chloride is dissolved in propylene glycol so that the concentration M of sodium chloride is 0.1 mol / L or more and less than 0.4 mol / L; When the temperature of the electrolytic polishing solution is T (unit: K), the concentration of the sodium chloride is M (unit: mol / L), the electrolytic voltage is V (unit: V), and the electrolytic time for electrolytic polishing the base material is t (unit: min), the base material is used as an anode and the electrolytic voltage is applied to electrolytically polish the base material under the condition that the parameter E represented by the following formula (1) is 6.5 or more and 100 or less, thereby forming the polished surface on the surface of the base material. E = (T × V 1.23 ×t) / (100000×M) ···(1)
[0013] In the manufacturing method, by adopting conditions in which the concentration M of sodium chloride in the electrolytic polishing solution and the value E in the formula (1) are within the specific ranges, electrolytic polishing can be performed using propylene glycol, which is environmentally friendly, easy to handle, and highly safe. Furthermore, by performing electrolytic polishing under the specific conditions, a polished surface with high specularity can be formed.
[0014] [Base material] The shape of the base material constituting the anode is not particularly limited, and any shape such as a plate, a block, or a cylinder can be appropriately selected. The surface of the base material may be flat or curved. In addition, the surface of the base material may have a recess or a protrusion, or may have a hole. The base material is subjected to machining, cutting, or other processing, and then electrolytic polishing.
[0015] The material of the base material in the aluminum material can be appropriately selected from the group consisting of aluminum and aluminum alloys depending on the application of the aluminum material.
[0016] More specifically, the aluminum constituting the base material of the aluminum material may be, for example, 1000 series aluminum having a chemical composition represented by alloy numbers A1050, A1060, A1070, A1080, A1085, A1200, or the like, or high purity aluminum with a purity of 99.99% (4N), 99.999% (5N), 99.9999% (6N), or the like.
[0017] As the aluminum alloy, a 2000 series aluminum alloy, a 3000 series aluminum alloy, a 4000 series aluminum alloy, a 5000 series aluminum alloy, a 6000 series aluminum alloy, a 7000 series aluminum alloy, or an 8000 series aluminum alloy can be used. When it is desired to increase the strength of the aluminum material, the base material can be made of a 5000 series aluminum alloy, a 6000 series aluminum alloy, or a 7000 series aluminum alloy.
[0018] More specifically, the 5000 series aluminum alloy constituting the base material of the aluminum material can be, for example, an aluminum alloy having a chemical composition represented by alloy number A5021, A5043, A5050, A5052, A5124, A5254, A5454, A5456, A5082, A5083, A5182, etc.
[0019] As the 6000 series aluminum alloy constituting the base material of the aluminum material, for example, aluminum alloys having chemical components represented by alloy numbers A6101, A6060, A6061, A6062, A6063, A6082, etc. can be used.
[0020] As the 7000 series aluminum alloy constituting the base material of the aluminum material, for example, aluminum alloys having chemical components represented by alloy numbers A7204, A7010, A7050, A7075, A7020, A7475, A7178, etc. can be used.
[0021] The base material may be subjected to pretreatment such as cleaning and degreasing prior to electrolytic polishing, if necessary.
[0022] The electrolytic polishing solution is prepared by dissolving sodium chloride in propylene glycol. The concentration M of sodium chloride in the electrolytic polishing solution is in the range of 0.1 mol / L or more and less than 0.4 mol / L. If the concentration M of sodium chloride is too high, for example, white spots may occur on the polished surface formed on the base material. For this reason, from a macroscopic perspective, the specularity of the polished surface is reduced, which is undesirable. The concentration M of sodium chloride is preferably 0.1 mol / L or more and 0.3 mol / L or less, and more preferably 0.15 mol / L or more and 0.25 mol / L or less. In this case, a glossy polished surface can be more easily formed.
[0023] The base material is immersed in the prepared electropolishing solution as an anode, and the counter electrode (cathode) is also immersed in. The base material and the counter electrode are connected to a DC power source.
[0024] The material constituting the counter electrode is not particularly limited, and can be appropriately selected from, for example, titanium, platinum, stainless steel, copper, etc. The shape of the counter electrode is not particularly limited, and can be appropriately selected from any shape such as a plate shape, a cylinder shape, etc.
[0025] The base material immersed in the electrolytic polishing solution is electrolytically polished under the condition that the parameter E expressed by the following formula (1) is 6.5 or more and 100 or less, where T (unit: K) is the temperature of the electrolytic polishing solution, M (unit: mol / L) is the concentration of sodium chloride, V (unit: V) is the electrolytic voltage, and t (unit: min) is the electrolytic time for electrolytic polishing the base material. E = (T × V 1.23 ×t) / (100000×M) ···(1)
[0026] The temperature T of the electrolytic polishing solution when electrolytic polishing is performed affects the amount of dissolution from the base material into the electrolytic polishing solution. When the temperature T of the electrolytic polishing solution is low, the amount of dissolution from the base material into the electrolytic polishing solution tends to be small, and when the temperature T of the electrolytic polishing solution is high, the amount of dissolution from the base material into the electrolytic polishing solution tends to be large. In addition, the electrolytic voltage V contributes to the driving force when the surface of the base material dissolves into the electrolytic polishing solution. When the electrolytic voltage V is low, the efficiency of electrolytic polishing decreases, and when the electrolytic voltage V is high, the dissolution from the base material into the electrolytic polishing solution tends to be promoted. The electrolytic time t affects the stability of the thickened layer in which the Al-based compound is thickened on the surface of the base material. When the electrolytic time t is short, the specularity of the polished surface decreases because a stable thickened layer is difficult to form, and when the electrolytic time t is long, the specularity of the polished surface tends to decrease. By electrolytically polishing the base material under conditions in which E represented by the above formula (1) is 6.5 or more and 100 or less, preferably 11.7 or more and 84.5 or less, and more preferably 23.3 or more and 84.5 or less, the efficiency of electrolytic polishing can be improved and the polished surface can be easily made mirror-finished.
[0027] From the viewpoint of workability, the temperature T of the electropolishing solution is preferably 273K or more and less than 313K. That is, by having the temperature T of the electropolishing solution be 0°C or more and 40°C or less, the efficiency of electropolishing can be further improved. From the same viewpoint, the temperature T of the electropolishing solution is more preferably 283K or more and 310K or less, that is, 10°C or more and 37°C or less, and further preferably 298K or more and 308K or less, that is, 25°C or more and 35°C or less.
[0028] By electrolytically polishing the base material under conditions where the parameter E represented by the above formula (1) is 6.5 or more and 100 or less with respect to the electrolytic voltage V, the efficiency of electrolytic polishing can be improved and the specularity of the polished surface can be improved.
[0029] Furthermore, the electrolysis voltage V is preferably 30 V or more and 100 V or less. By setting the electrolysis voltage V to preferably 30 V or more, more preferably 35 V or more, even more preferably 40 V or more, particularly preferably 55 V or more, and most preferably 60 V or more, the efficiency of electrolytic polishing can be further improved. Furthermore, by setting the electrolysis voltage V to preferably 100 V or less, more preferably 80 V or less, even more preferably 75 V or less, and particularly preferably 70 V or less, the specularity of the aluminum material can be more easily improved.
[0030] In configuring a preferred range of the electrolysis voltage V, it is possible to arbitrarily combine the above-mentioned upper and lower limits of the electrolysis voltage V. For example, the preferred range of the electrolysis voltage V may be 35V or more and 75V or less, 40V or more and 80V or less, 55V or more and 75V or less, or 60V or more and 70V or less.
[0031] By electrolytically polishing the base material under conditions where the parameter E represented by the above formula (1) for the electrolysis time t is 6.5 or more and 100 or less, the specularity of the polished surface can be improved more easily.
[0032] Furthermore, the electrolysis time t is preferably 1 min or more and 60 min or less. By setting the electrolysis time t to preferably 1 min or more, more preferably 5 min or more, and even more preferably 10 min or more, the thickened layer in the electropolishing solution can be stabilized, so that the gloss of the aluminum material can be improved more easily. In addition, by setting the electrolysis time t to preferably 60 min or less, more preferably 40 min or less, and even more preferably 30 min or less, it is easier to avoid excessive dissolution of the surface of the aluminum material, so that the gloss of the aluminum material can be improved more easily.
[0033] In determining the preferred range of the electrolysis time t, the above-mentioned upper and lower limits of the electrolysis time t can be combined arbitrarily. For example, the preferred range of the electrolysis time t may be 5 min to 40 min, or 10 min to 30 min.
[0034] For the concentration M of sodium chloride, by electrolytically polishing the base material under conditions where the parameter E expressed by the above formula (1) is 6.5 or more and 100 or less, the specularity of the polished surface can be improved.
[0035] From the viewpoint of further improving the specularity and gloss of the polished surface, the electrolytic polishing conditions are more preferably a combination of the concentration M of sodium chloride in the electrolytic polishing solution of 0.15 mol / L or more and 0.25 mol / L or less, the temperature T of the electrolytic polishing solution of 298 K or more and 308 K or less, the electrolytic voltage V of 35 V or more and 75 V or less, the electrolytic time of 10 min or more and 30 min or less, and the parameter E of 11.7 or more and 84.5 or less. From the same viewpoint, the electrolytic polishing conditions are more preferably a combination of the concentration M of sodium chloride in the electrolytic polishing solution of 0.15 mol / L or more and 0.25 mol / L or less, the temperature T of the electrolytic polishing solution of 298 K or more and 308 K or less, the electrolytic voltage V of 55 V or more and 75 V or less, the electrolytic time of 10 min or more and 30 min or less, and the parameter E of 23.3 or more and 84.5 or less.
[0036] [Polished surface] The surface of the base material is provided with a polished surface that has been polished by electrolytic polishing. The arrangement of the polished surface on the base material is not particularly limited, and for example, the polished surface may be formed on the entire base material, or the polished surface may be formed on only a part of the base material. The average regular reflectance of the polished surface at a wavelength of 360 to 740 nm is preferably 65% or more, more preferably 70% or more, and particularly preferably 80% or more. EXAMPLES
[0037] An embodiment of the method for manufacturing the aluminum material will be described with reference to Fig. 1 and Fig. 2. As shown in Fig. 1, the aluminum material 1 of this embodiment has a base material 2 made of aluminum or an aluminum alloy, and a polished surface 3 formed on at least a part of the surface of the base material 2. The polished surface 3 is formed by polishing at least a part of the surface of the base material 2 by electrolytic polishing. The polished surface 3 may be formed on the entire surface of the base material 2, or the polished surface 3 may be formed on only a part of the surface of the base material 2.
[0038] The manufacturing method of the aluminum material 1 is, for example, as follows. First, as shown in Fig. 2, a base material 2 as an anode and a counter electrode 12 are immersed in an electrolytic polishing solution 11 poured into an electrolytic cell 10. Thereafter, the base material 2 and the counter electrode 12 are connected to a DC power source 13, and a DC voltage is applied to the base material 2 and the counter electrode 12, thereby subjecting the base material 2 to electrolytic polishing. In this manner, a polished surface 3 can be formed on the surface of the base material 2.
[0039] Table 1 shows specific examples of aluminum materials (test materials S1 to S17). First, the manufacturing method of test materials S1 to S13 will be described. As a base material, an aluminum plate made of high-purity aluminum with a purity of 99.999% and having a thickness of 0.5 mm is prepared. In Table 1, high-purity aluminum alloy with a purity of 99.999% is described as "5N".
[0040] A propylene glycol solution of sodium chloride with a sodium chloride concentration M of 0.2 mol / M is prepared as an electropolishing solution. A base material is immersed in this electropolishing solution as an anode. A platinum plate with a purity of 99.95% is immersed in the electropolishing solution as a counter electrode. The base material is subjected to electropolishing treatment with the temperature T of the electropolishing solution set to the temperature shown in Table 1, the electrolysis voltage V set to the voltage shown in Table 1, the electrolysis time t set to the time shown in Table 1, and the parameter E set to the value shown in Table 1. As a result of the above, test materials S1 to S13 shown in Table 1 can be obtained.
[0041] In addition, the test materials S14 to S17 shown in Table 1 have the same configuration as the test materials S1 to S13, except that the material of the aluminum plate constituting the base material is changed to aluminum or aluminum alloy having a chemical composition represented by the alloy symbol shown in Table 1. The manufacturing method of the test materials S14 to S17 is the same as the manufacturing method of the test material S4, except that the material of the aluminum plate constituting the base material is changed to aluminum or aluminum alloy having a chemical composition represented by the alloy symbol shown in Table 1, and an aluminum plate with a purity of 99.999% (5N) is used as the counter electrode during the electrolytic polishing treatment. Note that R1 to R7 shown in Table 1 are test materials for comparison with the test materials S1 to S17. The manufacturing method of the test materials R1 to R7 is the same as the manufacturing method of the test materials S1 to S13, except that the electrolytic polishing conditions are changed as shown in Table 1.
[0042] Next, the methods for evaluating the various properties of the test materials S1 to S17 and the test materials R1 to R7 shown in Table 1 will be described.
[0043] [Specular reflectance] The regular reflectance of an aluminum material can be calculated by subtracting the result not including regular reflection from the result of measurement of reflectance including regular reflection. The "regular reflectance" column in Table 1 shows the regular reflectance of test materials S1 to S17 and test materials R1 to R7 before and after polishing. The regular reflectance can be measured using a spectrophotometer conforming to JIS Z 8722 condition c (for example, the spectrophotometer "CM-5" manufactured by Konica Minolta, Inc.). The measurement diameter in the measurement of regular reflectance is φ3 mm, and a pulsed xenon lamp can be used as the light source.
[0044] In addition, the specular reflectance of the base material before electrolytic polishing is measured. Table 1 shows the specular reflectance of each test material as well as the specular reflectance of the base material before electrolytic polishing.
[0045] [Visual inspection] The polished surface of each test material is visually inspected for appearance and evaluated for the presence or absence of white spots. Table 1 shows the results of the appearance inspection for each test material. When the surface of the test material is visually observed, white spots 4 may be observed. The area where these white spots 4 are observed is observed under an SEM. Figure 3 shows an example of an SEM photograph of white spots 4. In Figure 3, the area surrounded by a dashed line corresponds to white spots 4.
[0046] Furthermore, Fig. 4 shows an enlarged SEM photograph of a region corresponding to the white dots 4. The white dots 4 have a diameter of 10 µm to 60 µm. As can be seen in Fig. 4, many fine pits 41 with a diameter of 3 µm or less are generated inside the white dots 4. As described above, the white dots 4 are an aggregate of the fine pits 41. It is presumed that the visible white dots 4 are generated by light scattering caused by the aggregate of the fine pits 41.
[0047] [Table 1]
[0048] As shown in Table 1, the test materials S1 to S17 are obtained by performing electrolytic polishing on the base material under conditions where the parameter E represented by formula (1) is 6.5 or more and 100 or less. Therefore, the regular reflectance of these test materials is 65.6% (test material S17) to 87.5% (test material S8). In addition, the occurrence of white spots 4 was not confirmed on the polished surface of the test materials S1 to S17. From these results, by adopting conditions where the concentration M of sodium chloride in the electrolytic polishing solution and the value of E in the formula (1) are within the specific range, electrolytic polishing can be performed using propylene glycol, which has a low environmental load, is easy to handle, and is highly safe. Furthermore, by performing electrolytic polishing under the specific conditions, a polished surface with good mirror properties can be formed.
[0049] As shown in Table 1, among the test materials S1 to S13 in which the aluminum plate constituting the base material is a high-purity aluminum alloy with a purity of 99.999%, the regular reflectance of the test materials S1 to S8 is a high value of 82% or more. Therefore, it is more preferable that the electrolytic polishing conditions are a combination of the concentration M of sodium chloride in the electrolytic polishing solution of 0.15 mol / L to 0.25 mol / L, the temperature T of the electrolytic polishing solution of 298 K to 308 K, the electrolytic voltage V of 35 V to 75 V, the electrolytic time of 10 min to 30 min, and the parameter E of 11.7 to 84.5.
[0050] Furthermore, the regular reflectance of the test materials S2, S4, S5, S7, and S8 was 87.3% (S2), 87.2% (S4), 87.4% (S5), 87.4% (S7), and 87.5% (S8), respectively. Therefore, it is more preferable that the electrolytic polishing conditions are a combination of the concentration M of sodium chloride in the electrolytic polishing solution of 0.15 mol / L or more and 0.25 mol / L or less, the temperature T of the electrolytic polishing solution of 298 K or more and 308 K or less, the electrolytic voltage V of 55 V or more and 75 V or less, the electrolytic time of 10 min or more and 30 min or less, and the parameter E of 23.3 or more and 84.5 or less.
[0051] On the other hand, the parameter E in the electrolytic polishing process of the test materials R1 to R5 does not fall within the condition of 6.5 to 100. Therefore, for the test materials R1 to R5, the regular reflectance is 61.8% or less (test material R5), and it is not possible to form a polished surface with sufficient specularity.
[0052] The parameter E in the electrolytic polishing process of the test materials R6 to R7 also deviates from the condition of 6.5 or more and 100 or less. As a result, the occurrence of white spots was confirmed on the polished surface, and it was not possible to obtain a polished surface with sufficient mirror finish.
[0053] The above describes the aspects of the method for manufacturing an aluminum material according to the present invention based on the examples. However, the specific aspects of the method for manufacturing an aluminum material according to the present invention are not limited to the aspects of the examples, and the configuration can be changed as appropriate within the scope that does not depart from the spirit of the present invention.
[0054] For example, the method for producing the aluminum material can take the following modes [1] to [4].
[0055] [1] A method for producing an aluminum material having a polished surface formed by electrolytic polishing on a surface of a base material made of aluminum or an aluminum alloy, comprising: The base material is immersed in an electropolishing solution in which sodium chloride is dissolved in propylene glycol so that the concentration M of sodium chloride is 0.1 mol / L or more and less than 0.4 mol / L; A method for producing an aluminum material, comprising the steps of: applying an electrolytic voltage to the base material as an anode to electrolytically polish the base material, thereby forming the polished surface on the surface of the base material, under conditions where a parameter E represented by the following formula (1) is 6.5 or more and 100 or less, where T (unit: K) is the temperature of the electrolytic polishing solution, M (unit: mol / L) is the concentration of the sodium chloride, V (unit: V) is the electrolytic voltage, and t (unit: min) is the electrolytic time for electrolytically polishing the base material. E = (T × V 1.23 ×t) / (100000×M) ···(1)
[0056] [2] The method for producing an aluminum material according to [1], wherein the temperature T of the electropolishing solution is 273 K or more and 313 K or less.
[0057] [3] The method for producing an aluminum material according to [1] or [2], wherein the electrolysis voltage V is 30 V or more and 100 V or less.
[0058] [4] The method for producing an aluminum material according to any one of [1] to [3], wherein the electrolysis time t is 1 min or more and 60 min or less. [Explanation of symbols]
[0059] 1. Aluminum material 2 Base material 3 Polished surface 11 Electrolytic polishing liquid
Claims
1. A method for producing an aluminum material having a polished surface formed by electrolytic polishing on a surface of a base material made of aluminum or an aluminum alloy, comprising: The base material is immersed in an electropolishing solution in which sodium chloride is dissolved in propylene glycol so that the concentration M of sodium chloride is 0.1 mol / L or more and less than 0.4 mol / L; A method for producing an aluminum material, comprising the steps of: applying an electrolytic voltage to the base material as an anode to electrolytically polish the base material, thereby forming the polished surface on the surface of the base material, under the condition that a parameter E represented by the following formula (1) is 6.5 or more and 100 or less, where T (unit: K) is the temperature of the electrolytic polishing solution, M (unit: mol / L) is the concentration of the sodium chloride, V (unit: V) is the electrolytic voltage, and t (unit: min) is the electrolytic time for electrolytically polishing the base material. E=(T×V 1.23 ×t) / (100000×M) ・・・(1)
2. The method for producing an aluminum material according to claim 1, wherein the temperature T of the electropolishing solution is 273 K or more and 313 K or less.
3. The method for producing an aluminum material according to claim 1 or 2, wherein the electrolysis voltage V is 30 V or more and 100 V or less.
4. The method for producing an aluminum material according to claim 1 or 2, wherein the electrolysis time t is 1 min or more and 60 min or less.
Citation Information
Patent Citations
Electrolytic polishing liquid, and method for producing metal product
JP2006348336A
Surface processing method of aluminum base material
JP2015006719A